Benefit of the Doubt : The Newberg Mystery Series #1 - Griffin, Neal C. (New York : Forge Books, 2015)
Former big-city cop Ben Sawyer, now a detective in the tiny Wisconsin town where he and his wife grew up, stumbles upon a web of corruption that gets him kicked off the force and his wife accused of murder, forcing him to turn to a fellow outcast for help.
Former big-city cop Ben Sawyer, now a detective in the tiny Wisconsin town where he and his wife grew up, stumbles upon a web of corruption that gets him kicked off the force and his wife accused of murder, forcing him to turn to a fellow outcast for help.
"A Tom Doherty Associates book."
Keywords: Police -- Wisconsin -- Fiction; FICTION / Mystery & Detective / Police Procedural; Police -- Wisconsin -- Fiction; Suspense fiction